The Psychological Capital and Anxiety Felt by Post-Market Fire Disaster Victims - Dian Fitria; Mustikasari Mustikasari; Ria Utami Panjaitan (Jurnal Ners, 2020)
Introduction: Traditional markets are a financial resource for traders. Fire disasters at the traditional markets will have a bad effect in terms of generating both financial and psychological problems. There is a lack of studies about the psychological problems experienced by traditional market fire victims. The aim of this study is to identify the correlation of psychological capital (hope, self-efficacy, resilience, and optimism) with the anxiety level among the victims of market fire disasters in Central Jakarta.Methods: This study used a cross-sectional approach with a non-probability sampling method. This study involved 174 market fire victims from Central Jakarta. The independent variables were psychological capital, which includes hope, self-efficacy, resilience, and optimism. The dependent variable was anxiety level. The instruments used the Hope scale, the General Self Efficacy scale, The 14-item Resilience scale (RS-14), the Life Orientation Test-Revised (LOT-R) scale and the Generalized Anxiety Disorder scale. The data analysis used an Independent T-Test, Chi-Square, and multiple logistic regression prediction modeling.Results: The more kiosks burned, the more that the informant’s anxiety increased by about4.845 times after applying a control factor of self-efficacy and optimism with a Wald value of 23.146.Conclusion: Psychological capital (self-efficacy and optimism) have a significant correlation with anxiety in the market fire disaster victims. Good self-efficacy and optimism can reduce the level of anxiety felt.  This study highlighted that psychological capital is a part of the disaster assessment as the basis for providing disaster nursing interventions.